(untitled) (Zaporizhzhia Historical Review, 2022)
One of the reforms, launched after the Ukrainian Revolution of Dignity, was eradication of totalitarian symbols from the public space and rethinking of the Soviet past. This reform was named decommunization. In spite of independence and constitutional norms evidencing the country’s sovereignty, democratic governance and the rule of law, a framework of human, social, economic, political and other rights, in the central, southern and eastern parts of Ukraine a lot of the Soviet toponyms and memorials still remained. They testified about direct connection with the Soviet authoritarian state, which included Ukraine as a colony for 70 years. One of the cities in the south-eastern part of Ukraine, where hundreds of such objects were kept, was Dnipropetrovsk, a large industrial center with about one million inhabitants. The process of decommunization in this city from 2014 to 2019 is analyzed in the present article.